RETRACTED PAPER: "The Effects of Globalisation on International Trade Models: A Research on China" - Ali İskan Toptancı (ZBW - Leibniz Information Centre for Economics, 2020)
*** RETRACTION NOTICE *** Title: "The Effects of Globalisation on International Trade Models: A Research on China" – Submitted by Ali İskan Toptancı on December 18, 2020 – Published in EconStor on December 18, 2020 – Withdrawn on April 21, 2021 – The EconStor team has decided to retract the paper referenced above submitted by Ali İskan Toptancı, because the paper contains substantial duplication of text from Ralph Wrobel (2020): "The 'China Effect': Changes in international trade patterns as reasons for rising 'Anti-Globalism'", Ordnungspolitische Diskurse No. 2020-1, Erfurt, Ordnungspolitisches Portal (OPO). http://ordnungspolitisches-portal.com/wp-content/uploads/2020/04/2020-1-Wrobel-China-Effect-1.pdf
Keywords: 330